Synergistic regulation of metal–organic cage architectures via temperature- and solvent-driven atropisomerism - Jiaqi Liang; Li-Jun Peng; Ke-Lin Zhu; Zhi-Ao Li; Xu-Lang Chen; Yu-Dong Yang; Qian Li; Qian-Nan Bi; Jie Cui; Ai-Jiao Guan; Tong-Ling Liang; Xiang Hao; et al. (Proceedings of the National Academy of Sciences, 2025)
Regulating multistimulus responses in artificial systems remains a challenge in smart material development. We present a versatile chemical switching system that precisely controls the self-assembly of metal–organic cages via temperature and solvent changes. The key component, cyclo[2](1,3-(4,6-dimethyl)benzene) (4-pyridine)[6](1,3-(4,6-dimethyl)benzene) ( CP2 ), was generated as three atropisomers ( 1 , 2 , and 3 ) with C s , C 1 , and C 2v symmetries. Thermally, metastable isomers ( 1 and 2 ) convert into the stable isomer ( 3 ), which reacts with Pd 2+ to form specific molecular cages. Depending on the solvent, either rectangular M 2 L 2 cages ( 5′ and 5 ) form in 1,4-dioxane or hexagonal M 3 L 3 cages ( 6 ) in 1,1′,2,2′-tetrachloroethane. The solvent dictates the cage type and enables reversible transformation between cages 5 and 6 . Additionally, cage 5 ′, formed from metastable isomer 1 , can switch to other cage types (i.e., 5 or 6 ) depending on temperature and solvent conditions. This multipathway system offers a precise strategy for controlling self-assembly in smart materials.